Impact of Vocational Training on Value Addition in Knowledge and Adoption of Rural Women - Pandey, Ankita; Gupta, Nishith; Pandey, Akanchha; Singh, Sarita (Indian Journal of Extension Education, 2017)
The present study was conducted by Krishi Vigyan Kendra, Dewas for three years i.e. 2011-12, 2012-13 and 2013-14 with  the objective to find out the effectiveness of vocational training programme on knowledge and adoption of value addition  of food grains, fruits and vegetables among rural women. The data revealed that just after completion of training, majority  (63.33%) of trainees were having high level of knowledge regarding value addition followed by 36.66 per cent  respondents having medium level of knowledge. After seven days of training, most (56.66%) of the trainees had medium  level of knowledge followed by high level (43.33%), while, none of the trainees had low level of knowledge. The results  clearly indicated that vocational training on value addition was effective in enhancing the knowledge and adoption of  trainee. Therefore, it could be implied that more and more such training programmes on value addition may be organized  which would benefit rural women in particular and farming community in general.
Keywords: Vocational training; Impact; Value Addition; Processing